Analysis of the Influence of Starting Materials and Processing Conditions on the Properties of W/Cu Alloys - Montealegre-Meléndez, Isabel (Materials (Basel), 2017)
In this work, a study of the influence of the starting materials and the processing time used to develop W/Cu alloys is carried out. Regarding powder metallurgy as a promising fabrication route, the difficulties in producing W/Cu alloys motivated us to investigate the influential factors on the final properties of the most industrially demanding alloys: 85-W/15-Cu, 80-W/20-Cu, and 75-W/25-Cu alloys. Two different tungsten powders with large variation among their particle size—fine (W(f)) and coarse (W(c)) powders—were used for the preparation of W/Cu alloys. Three weight ratios of fine and coarse (W(f):W(c)) tungsten particles were analyzed. These powders were labelled as “tungsten bimodal powders”. The powder blends were consolidated by rapid sinter pressing (RSP) at 900 °C and 150 MPa, and were thus sintered and compacted simultaneously. The elemental powders and W/Cu alloys were studied by optical microscopy (OM) and scanning electron microscopy (SEM). Thermal conductivity, hardness, and densification were measured. Results showed that the synthesis of W/Cu using bimodal tungsten powders significantly affects the final alloy properties. The higher the tungsten content, the more noticeable the effect of the bimodal powder. The best bimodal W powder was the blend with 10 wt % of fine tungsten particles (10-W(f):90-W(c)). These specimens present good values of densification and hardness, and higher values of thermal conductivity than other bimodal mixtures.